Le cinque lire dell’aquila e i fiordalisi del Commendatore: Primo Levi dal liceo alla laurea in Chimica, ai primi lavori negli anni 1935-1942 - Barbarulo, Maria Vittoria (Chimica nella Scuola, 2022)
As a student of the Turin Royal Classical High School Massimo D’Azeglio, the young Primo Levi was captivated by the potential of Chemistry in the academic year 1935/36. It was a complex period of history, marked by important and life-changing events at a national and European level. After enrolling in a Chemistry degree course and gaining excellent marks in the requisite examinations, Levi could not do degree thesis based on laboratory experiments, due to the anti-Jewish laws that came into force in 1938; he was forced instead to do a meta analysis of previous research. His degree, conferred in June 1941, was followed by a variety of widely differing professional experiences.